To solve a function like this, simply put the numerical value in place of the unknown variable for which you have to find the solution, for instance '-3' in this case.
g(x) = 2x-2
so to find g(-3), we just need to replace the x in the given expression by '-3'. Working is shown below:
g(x) = 2x-2
putting '-3' in place of x
g(-3) = 2(-3) - 2
g(-3) = -6 -2
g(-3) = -8
The answer is <span>B.The statement is true, but the inverse is false.
An acute angle is less than 90 degrees when talking about the terminal side. It inverse would be 360 - 43 = 317 degrees </span>
We have the following expression:
(27x 4 - 18x 3 + 9x 2) ÷ 3x
Dividing each term between 3x we have:
9x3 - 6x2 + 3x
We can check the result:
(9x3 - 6x2 + 3x) * (3x)
= (27x4 - 18x3 + 9x2)
Division OK.
Answer:
The result of the division is:
9x3 - 6x2 + 3x
Answer:
$3.21
Step-by-step explanation:
Please let me know if you want me to write an explanation for my answer :)